2020
DOI: 10.32793/jrdi.v4i2.527
|View full text |Cite
|
Sign up to set email alerts
|

Densitas tulang mandibula pengguna obat anti hipertensi calcium channel blocker (CCB) melalui radiograf panoramik

Abstract: Objectives: The purpose of this research was to describe radiographic density of mandibular bone in calcium channel blocker anti-hypertensive drug users. Bone density in the mandible is assessed from the trabecular. Panoramic radiograph is a routine examination that is often done in dentistry that can be used to assess changes in quality in the form of changes in bone density in users of anti-hypertensive calcium channel blockers Material and Methods: This research is a descriptive study of 21 panoramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…27 A research in Wistar rats given am insignificant changes in bone, 18 other stated amlodipine impairs the bone marrow mo antihypertensive drug therapy, there can be an alteration of bone quality due to the disruption of calcium metabolism. 1,8,17,18,20,21,23,24 However, the effects of amlodipine on calcium metabolism and bone density themselves are still debated. There have been many studies that examined the relationship between these two and some of them concluded that the relationship is inconsistent and contradictory, including the result of this study.…”
Section: Ionmentioning
confidence: 99%
“…27 A research in Wistar rats given am insignificant changes in bone, 18 other stated amlodipine impairs the bone marrow mo antihypertensive drug therapy, there can be an alteration of bone quality due to the disruption of calcium metabolism. 1,8,17,18,20,21,23,24 However, the effects of amlodipine on calcium metabolism and bone density themselves are still debated. There have been many studies that examined the relationship between these two and some of them concluded that the relationship is inconsistent and contradictory, including the result of this study.…”
Section: Ionmentioning
confidence: 99%
“…Panoramic radiograph is a routine examination in dentistry that could use to assess changes quality of bone density. 16 The criteria for elderly according to the Ministry of Health of the Republic of Indonesia are over 50 years of age including early age (50 -64 years) and over 65 years. 17 The WHO meeting in Africa at the Harare MDS Workshop in 2000 decided that the chronological age that is said to be old age is 60 years, and in 2001 it was revised to 50 years considering the different conditions in each country.…”
Section: Discussionmentioning
confidence: 99%
“…9 Hypertensive patients who consume antihypertensive medication such as amlodipine will affect their calcium levels, which subsequently impacts their bone condition and becomes a risk factor for bone fractures. 10 Amlodipine can also decrease bone quality by reducing the production of steroid hormones, thus reducing bone formation and decreasing the volume of trabecular and cortical bone in the mandible. 11 Panoramic radiography is one of the dental medicine techniques that can provide an image encompassing the teeth, maxilla, and mandible, allowing visualization of the inferior mandibular cortex.…”
mentioning
confidence: 99%
“…The examination of panoramic radiography is conducted using several qualitative and quantitative indices, namely mandibular cortical index (MCI), mental index (MI), panoramic mandibular index (PMI), and gonion antegonial index. 10,12 PMI is an index that provides results in the form of a comparison between the thickness of the mandibular cortex and the distance from the inferior mental foramen to the inferior border of the mandibular cortex. Therefore, this measurement method allows calculations to be performed despite variations in magnification by different researchers.…”
mentioning
confidence: 99%